CONTEXTUALIZATION OF MANHAJ TAHLILI (Quraish Shihab's Response to Contemporary Issues in the Interpretation of the Noble Qur'an) - Mariani; Achmad Abubakar; Sohrah; Muhammad Irham; Kamriah (Pascasarjana UIN Alauddin Makassar, 2026)
Contemporary Qur'anic interpretation faces a significant challenge in the form of a persistent gap between the revealed text and continuously evolving social realities. This article aims to examine in depth how M. Quraish Shihab contextualizes the tahlili approach in responding to contemporary issues through his monumental work, Tafsir Al-Misbah. The study employs a qualitative descriptive-analytic approach grounded in library research methodology. The primary data source is Tafsir Al-Misbah by M. Quraish Shihab, while secondary sources comprise a range of peer-reviewed journals, classical and modern works of Qur'anic exegesis, and other relevant supporting literature. Data were analyzed through content analysis and comparative-critical methods. Three principal findings emerge from this study: first, Quraish Shihab actualizes social verses by employing a contextualization mechanism that integrates linguistic, historical, and sociological approaches; second, the wasathiyah mindset serves as the epistemological framework for cultivating inclusive and humanistic human relations; and third, Quraish Shihab's exegesis functions simultaneously as social critique and as an instrument of moral reorientation for modern society. This study recommends that Quraish Shihab's contextual exegetical approach be adopted as a developmental model for Qur'anic studies in Indonesia, one that is responsive to contemporary social and cultural dynamics.